Long-range interactions in neuronal gene expression: evidence from gene targeting in the GABA(A) receptor beta2-alpha6-alpha1-gamma2 subunit gene cluster - Uusi-Oukari,M; Heikkila,J; Sinkkonen,ST; Makela,R; Hauer,B; Homanics,GE; Sieghart,W; Wisden,W; Korpi,ER (Mol Cell Neurosci, 2000)
Clustering of GABA(A) receptor alpha1, alpha6, beta2, and gamma2 subunit genes on mouse chromosome 11/human chromosome 5 may have functional significance for coordinating expression patterns, but until now there has been no evidence for cross-talk between the genes. However, altering the structure of the alpha6 gene, specifically expressed in the cerebellum, with neomycin gene insertions in two different experiments unexpectedly reduced the expression of the widespread alpha1 and beta2 genes in the forebrain. There were corresponding reductions in the levels of alpha1 and beta2 subunit proteins and in autoradiographic ligand binding densities to GABA(A) receptors in the forebrain of alpha6-/- mice. The gamma2 mRNA level was not changed, nor were beta3 and delta mRNAs. The data suggest that elements in the neo gene may have an influence over long distances in the GABA(A) subunit gene complex on as yet undefined structures coordinating the expression of the alpha1 and beta2 genes